Susceptibility of enterococcus faecalis biofilm to antibiotics and calcium hydroxide - Chai, W.L.; Hamimah, H.; Cheng Soo, C.; Sallam Atiya, A.; Abdullah, M. (2007)
The purpose of this study was to investigate the antimicrobial efficacy of six groups of antibiotics and calcium hydroxide against Enterococcus faecalis biofilm in a membrane filter model. Two-day-old E. faecalis (ATCC 29212) biofilm was exposed to ampicillin, co-trimoxazole, erythr omycin, oxytetracycline, vancomycin, vancomycin followed by gentamicin, Ca(OH)2, and phosphate-buffered saline (control). After 1 h of exposure, the antimicrobial activity was neutralized by washing each disc five times in PBS, and then the colony-forming units of the remaining viable bacteria on each disc were counted. The results revealed that only erythromycin, oxytetracycline and Ca(OH)2 showed 100 biofilm kill. An ANOVA with a Bonferroni post hoc test (P < 0.05) detected significant differences among the test agents, except in the ampicillin group versus the co-trimoxazole group. It is concluded that erythromycin, oxytetracycline and Ca(OH)2 are 100 effective in eliminating E. faecalis biofilm, whereas ampicillin, co-trimoxazole, vancomycin, and vancomycin followed by gentamicin are ineffective.